Education of Syrian refugee children : managing the crisis in Turkey, Lebanon, and Jordan - Culbertson, Shelly (RAND, 2015)
With four million Syrian refugees as of September 2015, there is urgent need to develop both short-term and long-term approaches to providing education for the children of this population. This report reviewed Syrian refugee education in the three neighboring countries with the largest population of refugees, Turkey, Lebanon, and Jordan, and analyzes four areas: access, management, society, and quality. Policy implications include prioritizing the urgent need to increase access to education among refugees; transitioning from a short-term humanitarian response to a longer-term development response; investing in both government capacity to provide education and in formal, quality alternatives to the public school systems; improving data in support of decisionmaking; developing a deliberative strategy about how to integrate or separate Syrian and host-country children in schools to promote social cohesion; limiting child labor and enabling education by creating employment policies for adults; and implementing particular steps to improve quality of education for both refugees and citizens.